Holes - Sachar, Louis 1954- (New York : Random House, 1998)
As further evidence of his family's bad fortune which they attribute to a curse on a distant relative, Stanley Yelnats is sent to a hellish correctional camp in the Texas desert where he finds his first real friend, a treasure, and a new sense of himself.
O
Originally published in a slightly different form in New York by Farrar, Straus and Giroux in 1998.
660
O
Keywords: Large type books; Juvenile delinquency -- Fiction; Homeless persons -- Fiction; Friendship -- Fiction; Buried treasure -- Fiction; Large type books